Emerging role of microRNAs in regulating macrophage activation and polarization in immune response and inflammation. Issue 3 (27th April 2016) - Wu, Xiao‐qin; Dai, Yao; Yang, Yang; Huang, Cheng; Meng, Xiao‐ming; Wu, Bao‐ming; Li, Jun
Summary: Diversity and plasticity are hallmarks of macrophages. Classically activated macrophages are considered to promote T helper type 1 responses and have strong microbicidal, pro‐inflammatory activity, whereas alternatively activated macrophages are supposed to be associated with promotion of tissue remodelling and responses to anti‐inflammatory reactions. Transformation of different macrophage phenotypes is reflected in their different, sometimes even opposite, roles in various diseases or inflammatory conditions. MicroRNAs (miRNAs) have emerged as critical regulators of macrophage polarization (MP). Several miRNAs are induced by Toll‐like receptors signalling in macrophages and target the 3′‐untranslated regions of mRNAs encoding key molecules involved in MP. Therefore, identification of miRNAs related to the dynamic changes of MP and understanding their functions in regulating this process are important for discussing the molecular basis of disease progression and developing novel miRNA‐targeted therapeutic strategies. Here, we review the current knowledge of the role of miRNAs in MP with relevance to immune response and inflammation.